SISTEM INFORMASI DATA PENDUDUK MENGGUNAKAN FRAMEWORK LARAVEL BERBASIS WEB METODE WATERFALL PADA RW.01 RANGKAPAN JAYA PANCORAN MAS DEPOK - Muhamad Abizar; Samsoni (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Population data information system at Rw.01 Rangkapan Jaya uses Laravel Framework is an information for manage population data at Rw.01 Rangkapan Jaya which includes assistance system data, news at Rw.01, which is presented on a website that can be accesed by the admin and chairman of Rw.01 Rangkapan Jaya. In making this using media in the form of mysql software for databases with PHP a Programming language, the Laravel frameworkwith the concept of a model view controller, the methodized in this system is the waterfall method. From testing using the blackbox method that has been carried out, the information system can an well by users who use it. By using this information system, it is hoped that is will make it easier for Rw.01 Rangkapan Jaya devices or management to access the population data as a whole.